Application of a two-dimensional model for flooding and floodplain simulation: Case study in Tra Khuc-Song Ve river in Viet Nam - N.T.M. Linh; D.Q. Tri; T.H. Thai; N.Cao Don (International Association of Lowland Technology, 2018)
In this paper, a GIS-integrated two-dimensional (2D) model namely Telemac-2D was used to construct floodplain maps of the study area. Firstly, the NAM model based on characteristics of the watershed, rainfall and evaporation data were used to provide initial boundary conditions for the Telemac-2D model along with other parameters. In turn, this Telemac-2D was integrated with Digital Elevation Map (DEM) in ArcGIS for floodplain mapping. The calibration and validation results for water level showed a high conformity about the phase and water amplitude between calculated and observed data in the years 2007, 2009 and 2013. A comparison between floodplain mapping and information from surveys showed relative consistency in 2009 and 2013 with a low error. The evaluation criteria of NSE, PBIAS, and RSR had a goodness-of-fit between the simulated and the observed values. Finally, this paper has given us an opportunity to understand the application capabilities of the Telemac-2D model and GIS in floodplain and flood inundation mapping and in the study area.